Towards The Secure Internet of Things: Threats and Solution - Munirul Ula; Rizal Tjut Adek; Mukhlish (LPPM Universitas Malikussaleh, 2022)
The use of the Internet of Things (IoT) has recently become a worldwide trend, as this technology can connect various types of equipment such as sensors, cameras, and other devices via the internet. The broad adoption of various IoT technologies makes life easier and better for people. Internet of things applications has been widely used in Smart Building, Smart Vehicles, Construction Management, health management and many other applications. However, the IoT technology still has many flaws and weakness especially in its security and defense mechanism. This paper reviews and elaborate type of security vulnerabilities, issue and threats that IoT technology faces from academic research paper in the past 10 years. This review also aims to find the possible solutions proposed by researchers to overcome security weakness, threats and issue in IoT technology and its application. This research goal to provide guidelines for those who want to develop and improve IoT security. A systematic review was used as the methodology in this paper. The purpose of this systematic review is to survey the threats and vulnerabilities of IoT technology as reported in previous studies. This review also proposes a comprehensive countermeasure to the previously mentioned threats and weaknesses. This study's findings include the identification and classification of various threats in IoT, as well as methods for countermeasures against these attacks. It concludes with reviews of research gaps and future research directions to improve IoT security.